Spontaneous Rupture of Urinary Bladder in Puerperium: A Case Report - Biswas, Rahul; Begum, Zakia; Hussain, Md Tofazzal; Akhter, Parul; Alam, Samiya; Khan, Feroz Hasan (Faridpur Medical College Journal, 2026)
Background: Spontaneous bladder rupture during childbirth and postpartum period is potentially life-threatening and a rare event. Case report: Here, we are reporting a case of spontaneous urinary bladder rupture on 5th day of puerperium after vaginal delivery in a 20-year-old primi gravid woman who presented with huge urinary ascites, acute abdominal pain, anuria, renal failure. Emergency exploratory laparotomy with repair of ruptured urinary bladder was done to prevent further complications. Conclusion: Spontaneous bladder rupture in puerperium might be preventable while emergency laparotomy is lifesaving in such case. Faridpur Med. Coll. J. 2026;21(1):54-57